Gene Expression Profiles of Nondiabetic and Diabetic Obese Mice Suggest a Role of Hepatic Lipogenic Capacity in Diabetes Susceptibility - Lan, Hong; Rabaglia, Mary E.; Stoehr, Jonathan P.; Nadler, Samuel T.; Schueler, Kathryn L.; Zou, Fei; Yandell, Brian S.; Attie, Alan D. (Diabetes (New York, N.Y.), 2003)
Gene Expression Profiles of Nondiabetic and Diabetic Obese Mice Suggest a Role of Hepatic Lipogenic Capacity in Diabetes Susceptibility Hong Lan 1 , Mary E. Rabaglia 1 , Jonathan P. Stoehr 1 , Samuel T. Nadler 1 , Kathryn L. Schueler 1 , Fei Zou 2 , Brian S. Yandell 3 and Alan D. Attie 1 1 Department of Biochemistry, University of Wisconsin, Madison, Wisconsin 2 Department of Biostatistics, University of North Carolina, Chapel Hill, North Carolina 3 Department of Statistics and Horticulture, University of Wisconsin, Madison, Wisconsin Abstract Obesity is a strong risk factor for the development of type 2 diabetes. We have previously reported that in adipose tissue of obese ( ob/ob ) mice, the expression of adipogenic genes is decreased. When made genetically obese, the BTBR mouse strain is diabetes susceptible and the C57BL/6J (B6) strain is diabetes resistant. We used DNA microarrays and RT-PCR to compare the gene expression in BTBR- ob/ob versus B6- ob/ob mice in adipose tissue, liver, skeletal muscle, and pancreatic islets. Our results show: 1 ) there is an increased expression of genes involved in inflammation in adipose tissue of diabetic mice; 2 ) lipogenic gene expression was lower in adipose tissue of diabetes-susceptible mice, and it continued to decrease with the development of diabetes, compared with diabetes-resistant obese mice; 3 ) hepatic expression of lipogenic enzymes was increased and the hepatic triglyceride content was greatly elevated in diabetes-resistant obese mice; 4 ) hepatic expression of gluconeogenic genes was suppressed at the prediabetic stage but not at the onset of diabetes; and 5 ) genes normally not expressed in skeletal muscle and pancreatic islets were expressed in these tissues in the diabetic mice. We propose that increased hepatic lipogenic capacity protects the B6- ob/ob mice from the development of type 2 diabetes. Footnotes Address correspondence and reprint requests to Alan D. Attie, Department of Biochemistry, University of Wisconsin-Madison, 433 Babcock Dr., Madison, WI, 53706. E-mail: attieatbiochem.wisc.edu . Received for publication 16 October 2002 and accepted in revised form 18 November 2002. Additional information for this article can be found in an online appendix at http://diabetes.diabetesjournals.org . ACO, Acyl CoA oxidase; C T , threshold cycle; dChip, DNA-Chip analyzer; IL, interleukin; PEPCK, phosphoenopyruvate carboxykinase; PPAR-α, peroxisome proliferator–activator receptor-α; SREBP, sterol regulatory element binding protein; TG, triglyceride. DIABETES